Complement Component 3 Adapts the Cerebrospinal Fluid for Leptomeningeal Metastasis - Boire, Adrienne; Zou, Yilong; Shieh, Jason; Macalinao, Danilo G; Pentsova, Elena; Massagué, Joan (Cell, 2017)
We molecularly dissected leptomeningeal metastasis, or spread of cancer to the cerebrospinal fluid (CSF), which is a frequent and fatal condition mediated by unknown mechanisms. We selected lung and breast cancer cell lines for the ability to infiltrate and grow in CSF, a remarkably acellular, mitogen-poor metastasis microenvironment. Complement component 3 (C3) was upregulated in four leptomeningeal metastatic models and proved necessary for cancer growth within the leptomeningeal space. In human disease, cancer cells within the CSF produced C3 in correlation with clinical course. C3 expression in primary tumors was predictive of leptomeningeal relapse. Mechanistically, we found that cancer-cell-derived C3 activates the C3a receptor in the choroid plexus epithelium to disrupt the blood-CSF barrier. This effect allows plasma components, including amphiregulin, and other mitogens to enter the CSF and promote cancer cell growth. Pharmacologic interference with C3 signaling proved therapeutically beneficial in suppressing leptomeningeal metastasis in these preclinical models.